Strategy For Achieving The Title Of Clean And Serving Bureaucratic Area (WBBM) (Multi-Site Study at BBPMP Central Java and BBPPMPV BOE Malang) - Muhammad Muhajir; Hari Nugraha; Sahirman Sahirman (PT Inovasi Pratama Internasional, 2026)
This study analyzes the implementation of the Integrity Zone (ZI) towards a Corruption-Free Area (WBK) and a Clean and Serving Bureaucratic Area (WBBM) through a comparative study on BBPMP Central Java Province (Site 1) and BBPPMPV BOE Malang (Site 2). This bureaucratic reform aims to create a clean, accountable, and serving government. This qualitative research with a multicase case study design uses in-depth interviews, observations, and documentation studies as data sources, which are then analyzed using the Miles, Huberman, and Saldana models. The findings of this research can be summarized in the acronym PRIMA, which includes: Committed Leadership, Cultural and Human Resources (HR) Reform, Digital Innovation and Service Systematization, Integrated Supervision Management, and Service Accountability and Satisfaction. Strong leadership commitment is a vital foundation at both sites, but the implementation strategies and key challenges are different. BBPMP Central Java faces a dominant challenge on the aspect of human factors (changes in employee mindsets) and therefore focuses on human resource development. On the other hand, BBPPMPV BOE Malang, which already has the foundation of ISO 9001 quality management version 2000, tends to focus more on digitalization-based service innovation. The conclusion of this study confirms that there is no single formula for the success of ZI; Adaptive strategies rely heavily on the initial diagnosis of constraints and capabilities of the organization. Experience with external quality standards such as ISO can serve as a prerequisite that accelerates the adoption of ZI and shifts the focus of constraints from human factors to system optimization through technology. This research contributes to enriching the literature on bureaucratic reform by highlighting the dynamics of change, the role of initial capabilities, and the importance of contextual analysis in the formulation of effective ZI strategies